RETRACTED: Numerical study of 2D and 3D flow after NASA 4412 airfoil - Madaliev Murodil; Usmonov Mavlonbek; Fayzullaev Jamshid; Khusanov Yunusali; Radjapov Komil; Sattorov Abdusalom; Jalilov Inomjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001